Estimation of characteristic period for energy based seismic design - Hancioglu, Baykal; Polat, Zekeriya; Kircil, Murat Serdar (AMER INST PHYSICS, 2008)
Estimation of input energy using approximate methods has been always a considerable research topic of energy based seismic design. Therefore several approaches have been proposed by many researchers to estimate the energy input to SDOF systems in the last decades. The characteristic period is the key parameter of most of these approaches and it is defined as the period at which the peak value of the input energy occurs. In this study an equation is proposed for estimating the characteristic period considering an extensive earthquake ground motion database which includes a total of 268 far-field records, two horizontal components from 134 recording stations located on both soft and firm soil sites. For this purpose statistical regression analyses are performed to develop an equation in terms of a number of structural parameters, and it is found that the developed equation yields satisfactory results comparing the characteristic periods calculated from time history analyses of SDOF systems.
Keywords: predominant period; characteristic period; seismic energy; SPECTRUM; INPUT; DISPLACEMENT; STRENGTH; DEMAND; SITES; Construction & Building Technology; Geochemistry & Geophysics; Engineering; Materials Science